A Molecular Ferroelectric Thin Film of Imidazolium Perchlorate That Shows Superior Electromechanical Coupling1. (1st April 2014) - Zhang, Yi; Liu, Yuanming; Ye, Heng‐Yun; Fu, Da‐Wei; Gao, Wenxiu; Ma, He; Liu, Zhiguo; Liu, Yunya; Zhang, Wen; Li, Jiangyu; Yuan, Guo‐Liang; Xiong, Ren‐Gen
Abstract Molecular ferroelectric thin films are highly desirable for their easy and environmentally friendly processing, light weight, and mechanical flexibility. A thin film of imidazolium perchlorate processed from aqueous solution is an excellent molecular ferroelectric with high spontaneous polarization, high Curie temperature, low coercivity, and superior electromechanical coupling. These attributes make it a molecular alternative to perovskite ferroelectric films in sensing, actuation, data storage, electro‐optics, and molecular/flexible electronics.